A new emittance selection system to maximize beam transmission for low‐energy beams in cyclotron‐based proton therapy facilities with gantry. Issue 12 (29th October 2021) - Maradia, Vivek; Meer, David; Weber, Damien Charles; Lomax, Antony John; Schippers, Jacobus Maarten; Psoroulas, Serena
Abstract: Purpose: In proton therapy, the potential of using high‐dose rates in the cancer treatment is being explored. High‐dose rates could improve efficiency and throughput in standard clinical practice, allow efficient utilization of motion mitigation techniques for moving targets, and potentially enhance normal tissue sparing due to the so‐called FLASH effect. However, high‐dose rates are difficult to reach when lower energy beams are applied in cyclotron‐based proton therapy facilities, because they result in large beam sizes and divergences downstream of the degrader, incurring large losses from the cyclotron to the patient position (isocenter). In current facilities, the emittance after the degrader is reduced using circular collimators; however, this does not provide an optimal matching to the acceptance of the following beamline, causing a low transmission for these energies. We, therefore, propose to use a collimation system, asymmetric in both beam size and divergence, resulting in symmetric emittance in both beam transverse planes as required for a gantry system. This new emittance selection, together with a new optics design for the following beamline and gantry, allows a better matching to the beamline acceptance and an improvement of the transmission. Methods: We implemented a custom method to design the collimator sizes and shape required to select high emittance, to be transported by the following beamline using new beam optics (designed with TRANSPORT) to maximize acceptance matching. For predicting the transmission in the new configuration (new collimators + optics), we used Monte Carlo simulations implemented in BDSIM, implementing a model of PSI Gantry 2 which we benchmarked against measurements taken in the current clinical scenario (circular collimators + clinical optics). Results: From the BDSIM simulations, we found that the new collimator system and matching beam optics results in an overall transmission from the cyclotron to the isocenter for a 70 MeV beam of 0.72%. This is an improvement of almost a factor of 6 over the current clinical performance (0.13% transmission). The new optics satisfies clinical beam requirements at the isocenter. Conclusions: We developed a new emittance collimation system for PSI's PROSCAN beamline which, by carefully selecting beam size and divergence asymmetrically, increases the beam transmission for low‐energy beams in current state‐of‐the‐art cyclotron‐based proton therapy gantries. With these improvements, we could predict almost 1% transmission for low‐energy beams at PSI's Gantry 2. Such a system could easily be implemented in facilities interested in increasing dose rates for efficient motion mitigation and FLASH experiments alike.